A toxicomania como paradigma do entorpecimento pulsional e o gozo autista do corpo - Thales Siqueira de Carvalho (2012)
The drug addiction is a form of drug use, which becomes an excessive and dysregulated habit, that the individual presents great difficulty to abstain. In it, the others and the ideals seem excluded from the sight of the subject. In clinical work with drug addicted patients, we are constantly placed before impasses that jeopardize the progress of treatment as, for example, the indifference to the risks of death, very little adherence to treatment and the prevalence of the act rather than the words. Although taking into consideration these points, we chose as the object of this research, the autoerotic relationship of the drug addictedsubject with the body, taking it as a paradigm of the addictive structure of the drive itself which is present in every subject, but in different degrees and from our point of view, potentiated by the contemporary social setting. Thus, the increasing number of cases of compulsive additions, not only drug addiction, sets in our times, marked by excessive permissiveness to jouissance, a paradigm of the numbing and exhilarating character of the drive itself. We ask if it exists in this context a way of satisfying the body outside the symbolic marks, a jouissance of the organism, which requires satisfaction in the drive assemblage of the subjects and that, in cases of drug abuse, would set up as the pivot of intoxication. We question this taking into consideration that, given the ineffectiveness of t heir psychological resources to cope with life in the body, body that escapes death by the use of the word, the addicted subject would experiment a "pure auto-erotism" without the use of fantasy. This way of operation leads to the idea of a generalized autism, which means an autism put to every subject, but that, in drug abuse, would find a prevalence.